Relationship between Mosquito Nest Eradication Behavior and the Habit of Using Mosquito Repellent Against Dengue Hemorrhagic Fever in Pekat Village, Sumbawa District, Sumbawa Regency - Abdul Hamid; Hamdin Hamdin (Jurnal Penelitian Pendidikan IPA, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted by the Aedes Aegypti mosquito, DHF also occurs regularly and affects all age groups. This disease is related to people's behavior and the conditions or circumstances of the surrounding environment. This study aims to determine the relationship between mosquito nest eradication behavior and the habit of using mosquito coils on the incidence of DHF in Pekat Village, Kec. Sumbawa Regency Sumbawa. The type of research used in this research is an analytical survey using a case control research design. The results of the study based on the results of the Chi-Square test (X2) showed that there was a significant relationship between the practice of eradicating mosquito nests and the incidence of DHF (p value = 0.035), while the OR calculation results obtained OR = 0.267 indicating that the respondent's confidence interval (CI) was 95 %= 0.78-0.930. From these results it can be interpreted that eradicating mosquito nests is not a risk factor for DHF. The results of the Chi-Square test (X2) showed a significant relationship between the habit of using mosquito coils and the incidence of DHF (p value = 0.033), while the OR calculation results obtained OR = 0.260 by showing the respondent's habit of using mosquito coils Confidential Interval (CI) 95% = 95% = 0.73-0.921. From these results it can be interpreted that the habit of using mosquito coils is not a risk factor for DHF.